2017
DOI: 10.3389/fmicb.2017.02318
|View full text |Cite
|
Sign up to set email alerts
|

CTX-M-15-Producing E. coli Isolates from Food Products in Germany Are Mainly Associated with an IncF-Type Plasmid and Belong to Two Predominant Clonal E. coli Lineages

Abstract: Extended-spectrum beta-lactamases (ESBL) mediating resistance to 3rd generation cephalosporins are a major public health issue. As food may be a vehicle in the spread of ESLB-producing bacteria, a study on the occurrence of cephalosporin-resistantu Escherichia coli in food was initiated. A total of 404 ESBL-producing isolates were obtained from animal-derived food samples (e.g., poultry products, pork, beef and raw milk) between 2011 and 2013. As CTX-M-15 is the most abundant enzyme in ESBL-producing E. coli c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 45 publications
7
54
0
1
Order By: Relevance
“…The AMR determinants located on this integron were catA , bla OXA-1 , aac(6′)-Ib- cr, tetA and bla CTX-M-15 , conferring reduced susceptibility to chloramphenicol, ampicillin, streptomycin and ciprofloxacin, tetracycline and the third-generation cephalosporins. bla CTX-M-15 is the most abundant CTX-M gene in ESBL (extended-spectrum beta-lactamase)-producing E. coli causing human infections [ 8 ]. Analysis using blast n indicated that the AMR determinants on this transposon originated from two different fragments of DNA originating from different plasmids (Accessions: NC_014384.1 and MF353155.1) inserted into a fragment of DNA that originated from a strain of Enterobacter cloace ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The AMR determinants located on this integron were catA , bla OXA-1 , aac(6′)-Ib- cr, tetA and bla CTX-M-15 , conferring reduced susceptibility to chloramphenicol, ampicillin, streptomycin and ciprofloxacin, tetracycline and the third-generation cephalosporins. bla CTX-M-15 is the most abundant CTX-M gene in ESBL (extended-spectrum beta-lactamase)-producing E. coli causing human infections [ 8 ]. Analysis using blast n indicated that the AMR determinants on this transposon originated from two different fragments of DNA originating from different plasmids (Accessions: NC_014384.1 and MF353155.1) inserted into a fragment of DNA that originated from a strain of Enterobacter cloace ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, hybridizations on S1-PFGE gels revealed a unique bla CTX-M-15bearing IncF plasmid of the F31:A4:B1 formula in all ST617 and ST410 isolates and in one ST131 isolate. This very same bla CTX-M-15 IncF plasmid has regularly been identified in ST617 and ST410 in numerous animal species, foodstuffs, and countries worldwide (12)(13)(14)(15)(16), and in two ST44 and ST131 clinical isolates in the United States (17), thereby suggesting that this plasmid is a major genetic support for the dissemination of bla CTX-M-15 .…”
mentioning
confidence: 56%
“…Moreover, Nesme et al (2014) found ARGs from different environments (soil, ocean, and human faeces), and showed soil and human faeces shared ARGs (24/94), suggesting that genes flow between these environments (Nesme et al 2014). Also, several MGEs such as conjugative plasmids including incompatibility groups (Inc) F, A/C, N, HI2, I1, and K with specific insertion sequences (IS) such as ISEcp1 and ISCR1 elements are frequently reported with ESBLs (Ali et al 2016;Irrgang et al 2017Irrgang et al , 2018, indicating these IS elements are strongly associated with independent acquisition of the ESBL genes. IncN plasmids encoding CTX-M-1 have been found in bacteria isolated from pigs, farmers, and farm environments, such as manure and air, indicating the spread of conjugative IncN plasmids with bla CTX-M genes among pigs, farmers, and surroundings (Moodley and Guardabassi 2009).…”
Section: Horizontal Gene Transfer Among Bacteria At the Environmentalmentioning
confidence: 99%